2005
DOI: 10.1021/jp051702j
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport Model for Semiconductor Nanowire Growth

Abstract: We present a mass transport model based on surface diffusion for metal-particle-assisted nanowire growth. The model explains the common observation that for III/V materials thinner nanowires are longer than thicker ones. We have grown GaP nanowires by metal-organic vapor phase epitaxy and compared our model calculations with the experimental nanowire lengths and radii. Moreover, we demonstrate that the Gibbs-Thomson effect can be neglected for III/V nanowires grown at conventional temperatures and pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
236
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(267 citation statements)
references
References 18 publications
22
236
0
Order By: Relevance
“…It is necessary to note that, at high growth temperatures, the GaAs growth dominates through the twodimensional growth over the one-dimensional nanowire growth. 36 Due to the pre-existing {113} B faceted triangular pyramids associated with Au droplets, GaAs growth tends to flat the pyramids since we believe that, in this case, the GaAs growth is governed by kinetics (under high temperature growth and strong Ga supply), resulting in flatted but extended triangular pyramids, as shown in Figs. …”
Section: -mentioning
confidence: 97%
“…It is necessary to note that, at high growth temperatures, the GaAs growth dominates through the twodimensional growth over the one-dimensional nanowire growth. 36 Due to the pre-existing {113} B faceted triangular pyramids associated with Au droplets, GaAs growth tends to flat the pyramids since we believe that, in this case, the GaAs growth is governed by kinetics (under high temperature growth and strong Ga supply), resulting in flatted but extended triangular pyramids, as shown in Figs. …”
Section: -mentioning
confidence: 97%
“…In our case, wires with a length of 2 -3 m showed no pronounced tapering. Follow- ing this argument, we should conclude that with a diffusion length of about 40 nm, the mechanism limiting the growth should not be related to a short diffusion length, which is underestimated due to simplified assumptions in the model of Johansson et al 4 Besides a possible limitation due to the diffusion process itself, other mechanisms might be involved. One of these is related to the barriers that adatoms have to overcome when jumping from one surface to another ͑see Fig.…”
mentioning
confidence: 88%
“…͓DOI: 10.1063/1.2715119͔ Nanowires ͑NWs͒ have attracted much interest in recent time because of their potential for the fabrication of electronic and optoelectronic devices. [1][2][3] Different techniques such as metal-organic vapor phase epitaxy, 4 plasma-assisted molecular beam epitaxy ͑PAMBE͒, 5,6 and chemical beam epitaxy 7 have been used to grow a variety of semiconductor NWs with extremely high crystalline quality. For instance, GaN NWs grown by molecular beam epitaxy ͑MBE͒ show very strong luminescence efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Songmuang et al have systematically studied the nucleation and growth of GaN NRs on thin AlN wetting layers; 8 in particular, they have shown that the substrate temperature is the dominating parameter to control NR growth. Debnath et al have explained the observed strong increase of NR length with decreasing diameter employing a mass transport model 10 that was initially suggested by Johansson et al 11 for VLS growth of GaP NRs. It takes mass transport by diffusion on the NR sidewalls as a source for Ga adatoms into account and assumes the presence of a Ga droplet on the top surface.…”
Section: Introductionmentioning
confidence: 94%